Chinese language provision for ethnolinguistic minorities in Hong Kong primary and secondary schools: policy, practice, and phenomenology - Tsang, SCS (2021)
After the 1997 handover, policymakers in Hong Kong have instituted a series of language policies that emphasise the importance of the Chinese language to rebrand the postcolonial city as a ‘biliterate and trilingual’ financial hub in Asia. One unintended consequence, however, is that a burgeoning population of linguistically and culturally diverse students struggles to learn Chinese – i.e., Cantonese as the spoken code and Standard Written Chinese as the written code – as an additional language (CAL), which has escalated into a notable language education issue because later-life prospects are increasingly dependent upon their proficiency in Chinese as a majority language. Informed by findings of a systematic review carried out as part of the present study, and the Douglas Fir Group’s (2016) call for a transdisciplinary framework encompassing the micro, meso, and macro levels of additional language learning in a given milieu, a multi-dimensional, mixed-methods design was adopted to problematise CAL provision for ethnolinguistic minority students with CAL needs as the focal language policy and planning (LPP) phenomenon in post-1997 Hong Kong, as well as to particularise local realities with a cross-section of CAL instructional spaces and key participants therein.